Thrombosis and Haemostasis VTH Congress 1975
DOI: 10.1055/s-0039-1689653
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Characterization of Factor VIII-Activity Present in the Supernatant of Cryoprecipitates

Abstract: A relative higher percentage of the initial factor VIII activity is found in the supernatant of plasma from patients with von Willebrand’s Disease than in that from normals after cryoprecipitation. Moreover no factor VIII related antigen can be demonstrated in the supernatant after cryoprecipitate. A further study of the characteristics of this cryo-supernatant-factor VIII seemed therefore of interest.Cryosupernatant-factor VIII was partially purified by poly ethyl enegly col and ammoniumsulfate precipitation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This effect was exploited by us 3,4 and others 5,6 to increase fibrinogen content in blood bank cryoprecipitate for transfusion, as well as to moderate fibrinogen content in cryoprecipitate intermediate in FVIII concentrate production, where increased fibrinogen can affect subsequent purification and viral inactivation steps. As a result of this work, we also noted that the total recoverable FVIII after plasma temperature fluctuations was decreased in the cryosupernatant fraction, which has been shown to be associated with low‐molecular‐weight forms of von Willebrand factor and to be more labile than other forms of FVIII 7 . Fresh‐frozen plasma collected in the United Kingdom is not used for fractionation; nevertheless, we caution against assuming that the findings of Cardigan and colleagues are applicable to plasma collected in the EU where much of the recovered plasma is used for fractionation to FVIII and where these effects may come into play.…”
supporting
confidence: 54%
“…This effect was exploited by us 3,4 and others 5,6 to increase fibrinogen content in blood bank cryoprecipitate for transfusion, as well as to moderate fibrinogen content in cryoprecipitate intermediate in FVIII concentrate production, where increased fibrinogen can affect subsequent purification and viral inactivation steps. As a result of this work, we also noted that the total recoverable FVIII after plasma temperature fluctuations was decreased in the cryosupernatant fraction, which has been shown to be associated with low‐molecular‐weight forms of von Willebrand factor and to be more labile than other forms of FVIII 7 . Fresh‐frozen plasma collected in the United Kingdom is not used for fractionation; nevertheless, we caution against assuming that the findings of Cardigan and colleagues are applicable to plasma collected in the EU where much of the recovered plasma is used for fractionation to FVIII and where these effects may come into play.…”
supporting
confidence: 54%
“…However, there was a much greater fall in the FVIII recovered in the cryosupernatant. Over et al . (1978) suggested that the FVIII in the cryosupernatant has a relatively low molecular weight compared with the FVIII in the cryoprecipitate and that it is more labile.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a much greater fall in the FVIII recovered in the cryosupernatant. Over et al (1978) suggested that the FVIII in the cryosupernatant has a relatively low molecular weight compared with the FVIII in the cryoprecipitate and that it is more labile. The results from this study do show that more FVIII was lost from the cryosupernatant when units were stored at þ2 to þ6 C for 8 h. They contained 18 AE 4% of the plasma FVIII compared with 32 AE 6% which was seen in those prepared from unconditioned units.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 Functional assays with RIPA indicated that the HMW forms had disproportionately higher platelet aggregating activity. [71][72][73][74] This evaluation of VWF multimers saw a burst of reevaluation into VWD, and the identification of many "variant forms" of VWD, 36,[75][76][77][78][79][80][81] which was subsequently rationalized into an accepted, clinically relevant, classification and common nomenclature, 34 comprising a primary group of three VWD types (1, 2, and 3), and a secondary subgroup of four type 2 subtypes (2A, 2B, 2M, and 2N). At this time, the VWF antigen was measured by immunoprecipitating techniques, usually involving rabbit polyclonal antihuman VWF, and this test came to be called VWF:Ag (VWF "antigen").…”
Section: Early History Of Von Willebrand Diseasementioning
confidence: 99%